The Efficacy of ChatGPT-Assisted Learning in Teaching Writing Descriptive Text to Indonesian English as Foreign Language (EFL) Students - Soleman Dapa Taka (Universitas Islam Negeri Palopo, 2026)
This study investigates the efficacy of ChatGPT-assisted learning in teaching writing descriptive text to tenth-grade students at SMA Kristen Mercusuar Kupang, East Nusa Tenggara, Indonesia. With the rapid advancement of artificial intelligence (AI) technologies in educational settings, ChatGPT has emerged as a promising tool for supporting English as a Foreign Language (EFL) writing instruction. This study employed a quasi-experimental research design with a pre-test and post-test control group to measure the impact of ChatGPT integration on students' descriptive writing proficiency. A total of 60 tenth-grade students were divided into an experimental group (n = 30) and a control group (n = 30). The experimental group received writing instruction supplemented by ChatGPT interactions, while the control group followed the conventional teaching method. Data were collected through written descriptive text tasks and analyzed using an independent samples t-test. The results revealed that the experimental group demonstrated significantly higher post-test scores compared to the control group, with a mean difference of 12.4 points (p < 0.05). The ChatGPT-assisted group showed marked improvement in vocabulary use, grammatical accuracy, coherence, and descriptive language depth. Furthermore, student attitude questionnaires indicated a positive reception toward AI-assisted writing practice, with 83% of participants reporting increased confidence in English writing. These findings suggest that ChatGPT-assisted learning is an effective instructional strategy for enhancing descriptive writing skills among Indonesian EFL learners at the secondary school level. The study concludes with pedagogical implications for integrating AI tools into EFL writing classrooms and recommendations for future research.